Comparison of preseptal and retroseptal transconjunctival approaches in patients with isolated fractures of the orbital floor. Issue 3 (March 2018) - Barcic, Salem; Blumer, Michael; Essig, Harald; Schumann, Paul; Wiedemeier, Daniel B.; Rücker, Martin; Gander, Thomas
Abstract: Transconjunctival approach has become a standard procedure to access fractures of orbit and the infraorbital rim. The transconjunctival incision can be performed pre- or retroseptally. Both approaches have been described combined with modifications such as transcaruncular or detachment of the lateral canthus for wider exposure of the orbital walls and rim. Particularly concerning aesthetics, the transconjunctival approach shows advantages compared to the transcutaneous incisions, such as the transciliary and infraorbital access. Moreover, transconjunctival approach is preferred in the literature regarding lid retraction. In this study the preseptal approach is compared with the retroseptal approach concerning en- or ectropion, foreign body sensation and formation of symblepharon. In our collective complication rates were lower in the retroseptal transconjunctival group, although this was not statistically significant. Whether the preseptal or the retroseptal transconjunctival approach is selected, is rather based on the surgeon's preferences. Nevertheless, the retroseptal approach must be considered as advantageous alternative to the preseptal approach because of simpler surgical technique and the safer distance to the vulnerable lid apparatus.